Politeness as a national-cultural category - Болотнікова, Алла Петрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article gives an analysis of politeness as a national-cultural category. The definition of politeness as a communicative category which enables to shape a strategy of politeness in oral speech taking account of lexical-grammatical structure of language units is used as a basis. Much attention is given to the fact that understanding of politeness differs in various ethno-cultural communities and those peculiarities reflect in language and speech. The key priority in the article is the analysis of the Ukrainian model of politeness and its principles (following the rules of decency, attending to the interlocutor, showing interest in the interlocutor’s concerns, manifesting help to the recipient, showing respect for the partner in communication, appreciating independence, rights and freedoms of every person), as well as representation of the model of a polite Ukrainian. The author notes that an important characteristic of the national marking of politeness is the choice of the analysis scale: absolute (semantic) and relative (pragmatic), the first scale is concerned with the linguistic level, whereas the second one deals with the communicative level, therefore the relative (pragmatic) scale proves to be more important for the linguistic analysis of politeness within the scope of a specific linguistic-cultural community.